Analysis of Contract Implementation in E-Commerce Transactions: A Review Based on the Civil Code - Nugraha, Agung Setya; Kustanto, Anto; Widiastuti, Arum (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Digital transformation in the trade sector has driven significant changes in contract implementation patterns, particularly in e-commerce transactions. This study aims to analyze the implementation of e-commerce contracts from the perspective of the Civil Code (KUHPerdata), focusing on the validity requirements of contracts, evidence mechanisms, and legal protection for the parties involved. This research uses a normative juridical approach through analysis of national regulations, jurisprudence, and current legal literature. The research results show that although the Civil Code remains relevant in principle through the principle of consensualism and freedom of contract, digital contract forms such as click-wrap agreements pose challenges in terms of evidence and substantial justice, especially for consumers. There is disharmony between the Civil Code, the ITE Law, and the Consumer Protection Law that causes legal uncertainty. Therefore, regulatory harmonization and reinterpretation of classical norms are needed to ensure adaptive and proportional legal protection in the digital transaction ecosystem. This research emphasizes the importance of updating the civil law system to be able to answer the challenges of legal relations in the e-commerce era.